Peningkatan Kesehatan Pada Ibu Hamil Melalui Optimalisasi Protokol Kesehatan Di Era Pandemi Covid-19 Di Desa Selojari - Dhiyan Nany Wigati; Rizki Sahara (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2022)
Background: Stunting is a condition of toddlers who have a length or height that is less when compared to age. This condition is measured by a length or height that is more than minus two standard deviations of the median standard of child growth from WHO. Toddler stunting includes chronic nutritional problems caused by many factors such as socioeconomic conditions, maternal nutrition during pregnancy, pain in babies, and lack of nutritional intake in infants. Stunting toddlers in the future will have difficulty in achieving optimal physical and cognitive development (Kemenkes RI, 2018)   Purpose: Analyze the level of knowledge of pregnant women about antenatal care   Method: The design used in this community service activity is pre experimental design with one group pre test post test Results: Obtained results of knowledge level of pregnant women increased by 95.7% with good categories after being given intervention   Conclusion: In the class activities of pregnant women are carried out as one of the preventive measures to reduce the incidence of stunting, after the class of pregnant women with the target class of pregnant women, most of the level of maternal knowledge about stunting prevention has increased.